Impact of health literacy on shared decision making for prostate‐specific antigen screening in the United States. Issue 2 (9th November 2020) - Nguyen, David‐Dan; Trinh, Quoc‐Dien; Cole, Alexander P.; Kilbridge, Kerry L.; Mahal, Brandon A.; Hayn, Matt; Hansen, Moritz; Han, Paul K. J.; Sammon, Jesse D.
Abstract : Background: Current guidelines endorse shared decision making (SDM) for prostate‐specific antigen (PSA) screening. The relationship between a patient's health literacy (HL) and SDM remains unclear. In the current study, the authors sought to identify the impact of HL on the rates of PSA screening and on the relationship between HL and SDM following the 2012 US Preventive Services Task Force recommendations against PSA screening. Methods: Using data from the 2016 Behavioral Risk Factor Surveillance System, the authors examined PSA screening in the 13 states that administered the optional "Health Literacy" module. Men aged ≥50 years were examined. Complex samples multivariable logistic regression models were computed to assess the odds of undergoing PSA screening. The interactions between HL and SDM were also examined. Results: A weighted sample of 12.249 million men with a rate of PSA screening of 33.4% were identified. Approximately one‐third self‐identified as having optimal HL. Rates of PSA screening were found to be highest amongst the highest HL group (42.2%). Being in this group was a significant predictor of undergoing PSA screening (odds ratio, 1.214; 95% confidence interval, 1.051‐1.403). There was a significant interaction observed between HL and SDM ( P for interaction, <.001) such that higher HL was associated with a lower likelihood of undergoing PSA screening when SDM was present. Conclusions: In the uncertain environment of multiple contradictory screening guidelines, men who reported higher levels of HL were found to have higher levels of screening. The authors demonstrated that increased HL may reduce the screening‐promoting effect of SDM. These findings highlight the dynamic interplay between HL and SDM that should inform the creation and promulgation of SDM guidelines, specifically when considering patients with low HL. Abstract : The relationship between health literacy (HL) and shared decision making (SDM) demonstrates that increased HL may reduce the screening‐promoting effect of SDM. These findings highlight the dynamic interplay between HL and SDM that should inform the creation and promulgation of SDM guidelines, specifically when considering patients with low HL.